The Cold Road to Paris : Mapping Pathways Toward Sustainable Cooling for Resilient People and Economies by 2050 - World Bank (Washington, DC: World Bank, 2021)
The report provides insights into the relationship between cooling and already-agreed-upon climate and development goals; presents the barriers, critical step-changes, and solutions needed to accelerate innovation and transformation; proposes aspirational targets and actions for each decade with the aim of achieving net-zero GHG emissions from cooling applications by 2050; considers financing solutions; and suggests a framework for governments and the global cooling community to take action.